Ion channels of importance for the locomotor pattern generation in the lamprey brainstem-spinal cord - Grillner, Sten (Blackwell Science Inc, 2001)
The intrinsic function of the spinal network that generates locomotion can be studied in the isolated brainstem-spinal cord of the lamprey, a lower vertebrate. The motor pattern underlying locomotion can be elicited in the isolated spinal cord. The network consists of excitatory glutamatergic and inhibitory glycinergic interneurones with known connectivity. The current review addresses the different subtypes of ion channels that are present in the cell types that constitute the network. In particular the roles of the different subtypes of Ca(2+) channels and potassium channels that regulate integrated neuronal functions, like frequency regulation, spike frequency adaptation and properties that are important for generating features of the motor pattern (e.g. burst termination), are reviewed. By knowing the role of an ion channel at the cellular level, we also, based on previous knowledge of network connectivity, can understand which effect a given ion channel may exert at the different levels from molecule and cell to network and behaviour.